DETERMINAN INTENSI MENJADI WHISTLEBLOWING DENGAN PERLINDUNGAN HUKUM SEBAGAI VARIABEL MODERASI - Tiya Restika Putri; Muhammad Rasuli; Devi Safitri (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2022)
This study aims to examine the influence of organizational commitment, personal cost of reporting and moral intensity to whistleblowing intention with legal protection as moderating variabel. The sample used in this study is all employees who work in Bank Perkreditan Rakyat Riau Province. Collecting data of this study using a questionnaire submitted to 135 employees who work on Bank Perkreditan Rakyat Riau Province. From questionnaires distributed, 90 questionnaires can be completed and can be processed. The data analysis method used was multiple linear regression and moderated regression analysis (MRA), as well as data processing using SPSS software version 25. The results ofthe study with multiple linear regression analysis showed that organizational commitment, personal cost of reporting and moral intensity had a significant to whistleblowing intention. The analysis of the moderating variable shows that legal protection is only able to moderate the personal cost of reporting and is not able to moderate organizational commitment and moral intensity on the intensity of whistleblowing